The Struggle of Custom and Sharia: Classic Dilemma of Inheritance Settlement in Javanese and Minangkabau Ethnic Communities in Indonesia - Elfia, Elfia; Surwati, Surwati; Bakhtiar, Bakhtiar (Institut Agama Islam Negeri Curup, 2023)
This research aims at determining the reasons and causes for dividing inheritance before the death of the testator, as well as the implications of this inheritance division pattern on the heirs. The disagreement between custom (also known as adat) and Sharia creates an issue in the division of inheritance in Sungai Duo Village, South Solok Regency, Indonesia. In its principle, inheritance is divided after the testator dies. However, in Sungai Duo Village it applies differently, where inheritance is distributed before the testator passed away. This is empirical legal research using a qualitative legal approach, which was investigated through the Islamic inheritance law's perspectives. The data included primary data, which were obtained from interviews, and secondary data generated from document studies. Data were analyzed through several stages, including data reduction, data display, and verification. Based on the research findings, the reasons for dividing inheritance before the testator dies are: first, to avoid disputes between the heirs; second, lack of knowledge of the heirs concerning the Islamic inheritance system, resulting in inheritance division contradicts the provisions of Sharia; third, inheritance division pattern applied in society is dominated by customs that have been passed down for generations, and fourth, the diverse community of Minangkabau and Javanese ethnicity causes their inheritance division pattern to reflect their regional customs. The implication of this inheritance division pattern to the heirs is that there is peace for the heirs in terms of inheritance responsibility because they consider the heirs to have had the maturity and ability to manage the assets of their parents who are no longer able to manage these assets. So that it can improve their children's economies or serve as a supportÂ for those who are married. These findings alsoÂ prove the existence of legal duality, namely Islamic inheritance law and customary inheritance law. However, it appears that customary inheritance law is more prevalent than Islamic inheritance law.